Building the future : big teaming for audacious innovation - Edmondson, Amy C.; Reynolds, Susan Salter (BK business book., 2016)
Niccolò Machiavelli famously wrote, "There is nothing more difficult to take in hand, more perilous to conduct, or more uncertain in its success than to take the lead in the introduction of a new order of things." That's what this book is about--innovation far more audacious than a new way to find a restaurant or a smart phone you can wear on your wrist. Harvard professor Amy Edmondson and journalist Susan Salter Reynolds explore how to bring into being systems that transform human experience and make the world more livable and sustainable. This demands "big teaming": intense collaboration across professions and industries that may have completely different mindsets and even be antagonistic to each other. To do this successfully requires practicing new forms of leadership that combine an expansive vision with incremental action--not an easy balance. To reveal how pioneers build the future, Edmondson and Reynolds tell the story of Living PlanIT, an award-winning "smart city" start-up with a breathtakingly ambitious goal: building a showcase high-tech city from scratch to pilot its software. This meant a joint effort spanning a truly disparate group of software entrepreneurs, real estate developers, city government officials, architects, construction companies, and technology corporations. We get to know Living PlanIT's leaders and follow them and their partners through cycles of hope, exhaustion, disillusionment, pragmatism, and renewal. There are powerful lessons here for anyone, in any industry, seeking to transform the world.